Islamic Charitable Donations as an Instrument Policy for Poverty Reduction: Is it Effective for Indonesia? - Andi Triyawan (Universitas Darussalam Gontor, 2024)
The aim of this research is to examine factors that determine poverty reduction in Indonesia by way of undertaking business units of Islamic Charitable Donation as intervening variable. Data were randomly obtained from 244 business units of Islamic Charitable Donation managed by Pesantren Gontor (The largest Islamic Charitable Donation Institution in Indonesia) by employing Structural Equation Model (SEM) of Smart PLS 4 for analysis purposes. The study revealed that business units from the use of Islamic Charitable Donation (source of funds, profitability, Business Capital, Product Innovation, market need) showed a significant impact on Human Resources Development and poverty reduction. The finding of this study will be a benchmark for regulators to utilize Islamic Charitable Donation as an instrument of policy to reduce poverty in Indonesia. Adopting Islamic Charitable Donations as an instrument policy to reduce poverty is a formidable effort of regulators to ensure it is an effective tool. In addition, Islamic Charitable Donation is part of Islamic social funds that inseparable part of policy recommendation that led to maximizing other Islamic social funds to reduce poverty.